Preparing engineers for the challenges of community engagement. (2nd November 2017) - Harsh, Matthew; Bernstein, Michael J.; Wetmore, Jameson; Cozzens, Susan; Woodson, Thomas; Castillo, Rafael
ABSTRACT: Despite calls to address global challenges through community engagement, engineers are not formally prepared to engage with communities. Little research has been done on means to address this 'engagement gap' in engineering education. We examine the efficacy of an intensive, two-day Community Engagement Workshop for engineers, designed to help engineers better look beyond technology, listen to and learn from people, and empower communities. We assessed the efficacy of the workshop in a non-experimental pre–post design using a questionnaire and a concept map. Questionnaire results indicate participants came away better able to ask questions more broadly inclusive of non-technological dimensions of engineering projects. Concept map results indicate participants have a greater understanding of ways social factors shape complex material systems after completing the programme. Based on the workshop's strengths and weaknesses, we discuss the potential of expanding and supplementing the programme to help engineers account for social aspects central to engineered systems.